Who's up for early detection?. Issue 1 (28th January 2013) - Kirby, Roger
Abstract: The debate about the pros and cons of periodic health checks looks set to run and run – the value of advanced screening techniques will be reviewed critically in future issues of Trends . Copyright © 2013 John Wiley & Sons